Welcome to social theory - Brock, Tom (College teacher) (Los Angeles SAGE, 2023)
'Welcome to Social Theory' is exactly what students want: a lucid and engaging introduction to social theory that carefully uses images, examples and quotations to illustrate new ways of examining contemporary social life. Tom Brock's comprehensive and accessible style produces an indispensable guide to social theory that examine the major theoretical traditions from Marxism through to poststructuralism, and from feminism through to postcolonial theory, new materialism and posthumanism. 'Welcome to Social Theory' gives careful appraisal of classical ideas and debates in social theory and traces their impact on major contemporary theorists - including Michel Foucault, Pierre Bourdieu, Anthony Giddens, Margaret Archer, Judith Butler, bell hooks, Kimberlé Crenshaw, Edward Said, Homi Bhabha, Gayatri Spivak, Bruno Latour, Gilles Deleuze and Rosi Braidotti. This book offers crucial support to those looking to understand why social theory matters and how to use it, whether for reflective critique or to generate original research projects or to better understand the relationship between theories foundational to both the social sciences and arts and humanities. Social theory matters and this book shows why through relevant and compelling examples, including the gig economy, everyday sexism, digital black feminism, animal and environmental activism, stigma and discrimination against migrants, the need to decolonise the sociology curriculum and many more. Dr. Tom Brock is a Senior Lecturer of Sociology at Manchester Metropolitan University"--
Includes bibliographical references (pages 221-229) and index.
Keywords: Sociology